Experienced critical incidents affecting lead-times in the stroke care chain for low-priority patients – A qualitative study with critical incident technique. (September 2021) - Wennman, Ingela; Carlström, Eric; Fridlund, Bengt; Wijk, Helle
Highlights: The care chain for low-priority stroke patients suffers from time delays. Different types of critical incidents affect lead times along the full care chain. Critical incidents at one part of the care chain affect others in the overall process. There is a need for more knowledge of critical incidents in the stroke care chain. Abstract: Background: The time elapsing from the alarm being raised to arrival at the stroke unit is crucial for patients suffering a conceivable stroke. More knowledge is needed about critical incidents—both favourable and unfavourable—affecting the lead time in the care chain. Aim: To explore favourable and unfavourable critical incidents (CIs), affecting lead times in the care chain from the alerted ambulance to the stroke unit, as experienced by nurses, for low-priority patients suffering a conceivable acute stroke. Method: The study had an explorative descriptive design using a qualitative approach of Flanagan's Critical Incident Technique (CIT). Twenty-two nurses involved in the stroke care chain at a hospital in western Sweden were interviewed about their experiences regarding CIs influencing the lead time for low-priority patients. Results: There were 363 CIs identified related to human interactions and organizational structures. The types of CIs varied depending on where in the care chain they were experienced. Both favourable and unfavourable factors had an impact on the length of the lead time from alerted ambulance to stroke unit for lowpriority patients. Furthermore, CIs occurring both early and later in the care chain affected the whole process. Conclusions: There is a need for greater understanding within each interrelated department in the care chain about how CIs at one part of the care chain have an impact on another.